Arranging childcare in two Nordic countries: A comparison of ECEC start in Iceland and Sweden - Arnalds, Ásdís A.; Duvander, Ann-Zofie (Journal of Family Research, 2023)
Objective: The study examines the age children in Iceland and Sweden start Early Childhood Education and Care (ECEC) and how children's starting age is associated with parents' use of paid parental leave and their characteristics. Background: While children in Iceland have no legal rights to ECEC following the end of paid parental leave, in Sweden there is a continuum between paid parental leave and publicly subsidised ECEC. The leave period is also shorter in Iceland than in Sweden. The article addresses how these policy differences reflect the transition from paid parental leave to ECEC-start in the two countries. Method: The study uses survey data, collected among parents in Iceland and Sweden. Results: Children in Iceland have an earlier ECEC start than children in Sweden. This earlier start, however, has to do with the number of children being placed in family day care while waiting for a place in the public run preschools. Mothers in Iceland stretch the parental leave for a longer period than mothers in Sweden do, and in Iceland, there were variations in ECEC start depending on mothers’ labour force participation before childbirth and marital status, but not in Sweden. Conclusion: The lack of preschool at the end of paid parental leave creates challenges for a certain group of parents in Iceland, a situation parents in Sweden do not have to face. Fragestellung: Die Studie untersucht das Alter, in dem Kinder in Island und Schweden mit der frühkindlichen Betreuung, Bildung und Erziehung („ECEC“) beginnen, und wie das Eintrittsalter der Kinder mit der Inanspruchnahme von Elternzeit und den Merkmalen der Eltern zusammenhängt. Hintergrund: Während Kinder in Island nach dem Ende der bezahlten Elternzeit keinen Rechtsanspruch auf ECEC haben, gibt es in Schweden mehrere Möglichkeiten zwischen bezahltem Elternurlaub und öffentlich subventionierter ECEC. Die Dauer der Elternzeit ist in Island kürzer als in Schweden. Der Artikel untersucht, wie sich diese Unterschiede beim Übergang von bezahlter Elternzeit in die ...